Hubungan Antara Stres dengan Kejadian Emotional Eating pada Pekerja Yang Melanjutkan Pendidikan Ekstensi - Mentari Nur Pertiwi; Vera Wahyuni Ulandari (Yayasan Literasi Sains Indonesia, 2023)
Stress is the fourth most common noncommunicable disease in the world. Because stress has so many harmful consequences, the body defends itself as the coping stress mechanism. Emotional eating are eating behaviors that aren’t triggered by physical hunger, but as a result of certain emotional impulses. Emotional eating can lead to weight gain, which can lead to chronic illness till the end. Analyzing the relationship between stress levels and the prevalence of emotional eating in extension students of the Faculty of Public Health, University of Indonesia. This study used a quantitative design with a cross-sectional research method and correlation test with a 95% confidence level ( = 0.05). According to research findings, the majority of respondents (46.4%) experienced moderate emotional eating (32 of 69 respondents). In terms of stress, the majority of the correspondents who were studying and working reported a normal stress level of 33.3%. (23 out of 69 respondents). The relationship between the level of stress and the incidence of emotional eating in Extension Students FKM UI obtained a coefficient value of 0.398 with a p-value of 0.001, indicating that the two variables have a moderately strong positive relationship. There is a relation between stress levels and the incidence of emotional eating in extension students at the University of Indonesia's Faculty of Public Health.